SOCIO-PSYCHOLOGICAL PROBLEMS AND NEEDS OF MENTALLY RETARDED CHILDREN IN DISTRICTS FAISALABAD AND ISLAMABAD, PAKIATAN - T. Aslam; Z. Batool; N. Hashmi; K. Aslam (Journal of Animal and Plant Sciences, 2011)
God has gifted human beings with six major power of senses, if any one of these is absent or damaged in such a way that it is unable to perform its function, the person became handicapped. A cross sectional study of 120 mentally retarded children of age 6-18 years was conducted in Faisalabad and Islamabad districts by using convenient sampling technique. The purpose was to study the socio-psychological problems and needs of these children. Teachers at center and parents of these children were interviewed through a well structured questionnaire consisting of open ended and close ended questions. Study indicates that majority (79%) of the children belonged to low income families. The symptom of mental retardation was mostly by birth. It has been also observed that disability is a great problem not only for child but also for the family. Their future should be shaped in harmony and cooperation. Their lives should mature as they broaden their perspectives and gain new experience.
Keywords: Mentally retardation; socio-psychological factors; needs of mentally retarded children.